2012
DOI: 10.1590/s2179-64912012000200017
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and acquired immune deficiency syndrome: systematic review

Abstract: HIV/AIDS patients may present hearing loss. Thus, programs for prevention and treatment of AIDS must involve actions aimed at auditory health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…cardiovascular disease) could also have predisposed a higher referral rate in this selected population (Agrawal et al 2009;Lin et al 2011). Many of the individuals screened visited the PHC clinic for management of prominent diseases and conditions such as diabetes, tuberculosis, HIV/AIDS, hypertension and malaria, all from which hearing loss can arise (Araújo et al 2012;Seddon et al 2012;Assuiti et al 2013;Van der Westhuizen et al 2013). It was, however, beyond the scope of this study to establish relationships between the abovementioned risk factors and hearing loss at PHC level.…”
Section: Discussionmentioning
confidence: 97%
“…cardiovascular disease) could also have predisposed a higher referral rate in this selected population (Agrawal et al 2009;Lin et al 2011). Many of the individuals screened visited the PHC clinic for management of prominent diseases and conditions such as diabetes, tuberculosis, HIV/AIDS, hypertension and malaria, all from which hearing loss can arise (Araújo et al 2012;Seddon et al 2012;Assuiti et al 2013;Van der Westhuizen et al 2013). It was, however, beyond the scope of this study to establish relationships between the abovementioned risk factors and hearing loss at PHC level.…”
Section: Discussionmentioning
confidence: 97%
“…Most of our patients had experienced years of disease, potentially contributing to their sensorineural components . Exposure to rubella, measles, cytomegalovirus, and HIV might have contributed as well in a country with low immunization rates. Most worrying was the possibility that long‐term exposure to aminoglycoside ear drops had caused true SNHL.…”
Section: Discussionmentioning
confidence: 98%
“…We observed that research studies on hearing loss in children with HIV/AIDS prioritize the detection of hearing losses or reporting the patients' otologic and/or auditory manifestations without associating these with the possible factors that trigger them (2,10,14,15,26,27) . The opportunistic infections that can cause hearing losses are many, but the majority of studies report cases only to demonstrate the patients' clinical situation in relation to hearing loss (26,28,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Among the many alterations and/or complications that the HIV can cause, directly or indirectly, alterations in the auditory system stand out. Hearing loss (HL) of several types (conductive, neurosensory, and mixed) in individuals affected by this virus can be associated with opportunistic infections, ototoxic drugs, and the direct action of the virus upon the auditory system (2)(3)(4) . The audiological and otologic complaints most commonly reported in children infected by HIV, with or without HL, are otalgia, otorrhea, vertigo, and buzzing in the ears (3,4) .…”
Section: Introductionmentioning
confidence: 99%